2010
DOI: 10.1016/j.ccr.2010.05.025
|View full text |Cite
|
Sign up to set email alerts
|

A Synthetic Lethal Interaction between K-Ras Oncogenes and Cdk4 Unveils a Therapeutic Strategy for Non-small Cell Lung Carcinoma

Abstract: We have unveiled a synthetic lethal interaction between K-Ras oncogenes and Cdk4 in a mouse tumor model that closely recapitulates human non-small cell lung carcinoma (NSCLC). Ablation of Cdk4, but not Cdk2 or Cdk6, induces an immediate senescence response only in lung cells that express an endogenous K-Ras oncogene. No such response occurs in lungs expressing a single Cdk4 allele or in other K-Ras-expressing tissues. More importantly, targeting Cdk4 alleles in advanced tumors detectable by computed tomography… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
302
1
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 378 publications
(320 citation statements)
references
References 36 publications
15
302
1
2
Order By: Relevance
“…3,[5][6][7] Nonetheless, Cdk4 inhibition may be effective to prevent Myc-induced skin tumors, 8 Rasinduced breast cancer 9 or K-Ras-induced non-small-cell lung carcinoma. 10 These results suggest that Cdk inhibition may be exploited in clinical settings taking into consideration the cellular context of the tumor and the pathogenic spectrum of their mutations.…”
Section: Cell Cycle Entrymentioning
confidence: 99%
See 1 more Smart Citation
“…3,[5][6][7] Nonetheless, Cdk4 inhibition may be effective to prevent Myc-induced skin tumors, 8 Rasinduced breast cancer 9 or K-Ras-induced non-small-cell lung carcinoma. 10 These results suggest that Cdk inhibition may be exploited in clinical settings taking into consideration the cellular context of the tumor and the pathogenic spectrum of their mutations.…”
Section: Cell Cycle Entrymentioning
confidence: 99%
“…For instance, inhibition of Cdk4 prevents the development of lung tumors induced by K-Ras oncogene by triggering senescence, a permanent arrest in G0/G1. 10 Current data suggest that senescent cells may be cleared by an innate immune response, but the extent to which this may contribute to prevention of age-related pathologies and cancer is currently not clear.…”
Section: Cell Cycle Entrymentioning
confidence: 99%
“…In further support of this emerging theme, Amati and colleagues (Campaner et al 2010) observed that oncogenic stress caused by the Myc oncoprotein sensitizes Cdk2-deficient cells to undergo senescence in vitro and in vivo. Similarly, in advanced non-small-cell lung carcinoma driven by activation of oncogenic KRas, tumor progression is halted and senescence is induced upon genetic ablation of Cdk4 (Puyol et al 2010). The rising number of examples of enforced senescence in vivo justifies further exploration of this possibility by addressing several more clinically oriented questions.…”
Section: Restoration Of Cellular Senescence In Vivomentioning
confidence: 99%
“…KRAS mutations are negative prognostic indicators in NSCLC (10) and have been associated with poor response to drugs targeting EGFR in NSCLC and colorectal carcinoma (10)(11)(12). Despite many attempts, pharmacologic targeting of KRAS remains a challenge (13)(14)(15)(16)(17)(18). Recent studies have identified alterations in metabolic programming that are specific to RASmutant cells such as enhanced glucose uptake, decreased tricarboxylic acid (TCA) cycle activity and higher dependency on glutamine for biosynthetic reactions than RAS wild-type cells (19)(20)(21).…”
Section: Introductionmentioning
confidence: 99%